2002
DOI: 10.1080/00365540110080412
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte Depleted, Unscreened Blood Products Give a Low Risk for CMV Infection and Disease in CMV Seronegative Allogeneic Stem Cell Transplant Recipients with Seronegative Stem Cell Donors

Abstract: Leukocyte depletion (LD) by blood product filtration has been shown to be similarly effective to the use of screened, CMV seronegative blood products to prevent CMV disease in CMV seronegative allogeneic stem cell transplant (SCT) patients with CMV seronegative donors. The aim of this retrospective study was to determine the risk for development of CMV infection requiring preemptive therapy and for CMV disease if unscreened products treated by prestorage LD is used. Forty-nine consecutive patients transplanted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
27
0
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 15 publications
(7 reference statements)
2
27
0
4
Order By: Relevance
“…To reduce the risk for transmission of CMV, blood products from CMV-seronegative donors or leukocyte-reduced, filtered blood products should be used. [110][111][112] Recipients who are CMV seronegative before allogeneic HSCT should ideally receive a graft from a CMV-negative donor. Weighing the factor of donor CMV serostatus compared with other relevant donor factors, such as HLAmatch, is difficult.…”
mentioning
confidence: 99%
“…To reduce the risk for transmission of CMV, blood products from CMV-seronegative donors or leukocyte-reduced, filtered blood products should be used. [110][111][112] Recipients who are CMV seronegative before allogeneic HSCT should ideally receive a graft from a CMV-negative donor. Weighing the factor of donor CMV serostatus compared with other relevant donor factors, such as HLAmatch, is difficult.…”
mentioning
confidence: 99%
“…der Applikation von seronegativem Blut sind widersprüchlich. Einerseits wird beschrieben, dass die Leukozytendepletion der Verwendung HCMV-seronegativer, nicht leukozytenreduzierter Blutkomponenten äquivalent ist [55,62,63,116,119,[139][140][141][142][143][144][145][146]. Neue Studienergebnisse belegen, dass frisch serokonvertierte Spender die höchsten Viruskonzentrationen im Verlauf einer HCMV-Infektion haben.…”
Section: Möglichkeiten Zur Abtrennung Und Inaktivierung Von Infektionunclassified
“…An older study by Ljungman et al that included blood products that were leukoreduced by bedside leukofiltration also found no statistically significant difference in the rate of CMV infection in HSCT patients who were transfused with LR/CMV-seronegative blood products (9.1% versus 12.2% LR/CMV-untested). 60 Meta-analysis of the combined data from both of these studies similarly found no significant difference in the risk of TT-CMV infection in patients transfused using the "belt-and-suspenders" approach versus …”
mentioning
confidence: 97%